State‐of‐the‐art on the protection of FACTS compensated high‐voltage transmission lines: a review. Issue 1 (22nd February 2018) - Biswas, Sauvik; Nayak, Paresh Kumar
Abstract : In recent years, the inclusion of flexible AC transmission systems (FACTS)‐based compensating devices such as a thyristor‐controlled series capacitor (TCSC) and a unified power flow controller (UPFC) has been increased in high‐voltage power transmission systems due to numerous technical and economical benefits. However, the operation of such FACTS devices introduces harmonics and non‐linearity in power system and causes fast changes in line impedance. As a result, the most widely used fixed impedance setting based distance relaying scheme finds limitation in protecting such compensated lines. Significant research has been carried out in recent years to develop new algorithms and methods to address the problem. This paper presents a comprehensive review of recent developments in the protection of TCSC/UPFC compensated high‐voltage transmission lines. The relative merits and demerits of each of the available methods are also presented for comparison. Prior to detail review, the impact of TCSC/UPFC on distance protection is evaluated by using data generated through EMTDC/PSCAD on a 400 kV two‐bus test power system. This study can be useful to both academic researchers and practicing engineers to gain insight on the protection of FACTS compensated transmission lines and for further development of newer algorithms.